Utilization of Virtual Labs in Science Learning: An Alternative Solution for Student Practicals in Secondary Schools - Marbun, Juliaster; Akbar, Khoironi Fanana (Scientica Education Journal, 2025)
This study aims to describe the use of virtual labs in Natural Science (IPA) learning as an alternative solution to the limitations of practical implementation in secondary schools. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of teachers and students in secondary schools that have implemented virtual lab-based learning. The results of the study indicate that virtual labs are able to improve conceptual understanding, learning interest, and provide easy access to practical activities. However, there are still obstacles such as limited devices, internet networks, and digital readiness of teachers and students. This study confirms that virtual labs are a potential learning medium to support innovation in science learning, especially amidst the limitations of conventional laboratory facilities.